The impact of occupational stress factors on temporary work disability related to arterial hypertension and its complications. Issue 2 (3rd April 2017) - Lazaridis, Konstantinos; Jovanović, Jovica; Jovanović, Jovana; Šarac, Ivana; Jovanović, Stefan
Abstract : Aim. To determine which specific groups of occupational stress factors influence the duration of temporary work disability related to arterial hypertension and joint complications/co-morbidities. Methodology. Workers ( n = 1398; 1009 in the exposed group, 389 in the control group) with arterial hypertension who worked at one workplace for a minimum of 10 years were divided into 10 subgroups, depending on the presence of joint complications/co-morbidities. The intensity of seven groups of occupational stress factors, the total score of Occupational Stress Index (OSI) and the average number of lost working days during 1 year were analysed. Results. The number of lost working days due to arterial hypertension and joint complications/co-morbidities was significantly higher in the exposed group. In all subgroups of the exposed group there was a high correlation between the number of lost working days and the total OSI score. Specific occupational stress factors were associated with specific complications: High Demands with chronic myocardial infarction, Strictness with cerebral haemorrhage, Conflict/Uncertainty with cerebral infarction, Extrinsic Time Pressure with acute myocardial infarction, and Avoidance/Symbolic Aversiveness with non-insulin-dependent diabetes. Conclusion. There are specific groups of occupational stress factors which can influence the duration of work disability associated with certain complications and co-morbidities of arterial hypertension.